2012
DOI: 10.1523/jneurosci.5636-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Early Binding of Gaze, Gesture, and Emotion: Neural Time Course and Correlates

Abstract: Communicative intentions are transmitted by many perceptual cues, including gaze direction, body gesture, and facial expressions. However, little is known about how these visual social cues are integrated over time in the brain and, notably, whether this binding occurs in the emotional or the motor system. By coupling magnetic resonance and electroencephalography imaging in humans, we were able to show that, 200 ms after stimulus onset, the premotor cortex integrated gaze, gesture, and emotion displayed by a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
100
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 84 publications
19
100
2
Order By: Relevance
“…Of interest, once merged into a single percept, co-emitted social signals can take on new significance and certain combinations, notably those indicating the presence of threat, become more relevant than others. Typically, angry expressions are perceived as more threatening when associated with a direct gaze than with an averted gaze (Sander et al 2007; N' Diaye et al 2009;Sato et al 2010;Conty et al 2012). Despite the clear relevance of understanding the spatiotemporal characteristics of the mechanisms underlying the combination of social cues, the question of whether, when and how, directing one's attention towards a specific social signal impacts on its neural integration with other co-emitted social cues remains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of interest, once merged into a single percept, co-emitted social signals can take on new significance and certain combinations, notably those indicating the presence of threat, become more relevant than others. Typically, angry expressions are perceived as more threatening when associated with a direct gaze than with an averted gaze (Sander et al 2007; N' Diaye et al 2009;Sato et al 2010;Conty et al 2012). Despite the clear relevance of understanding the spatiotemporal characteristics of the mechanisms underlying the combination of social cues, the question of whether, when and how, directing one's attention towards a specific social signal impacts on its neural integration with other co-emitted social cues remains.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that the neural sources underlying social cues integration may be task demand-dependent (Graham and Labar 2012;Dumas et al 2013). While most of the functional Magnetic Resonance Imagery (fMRI) experiments revealed that the amygdala integrated emotion and gaze when participants were required to attend to the emotional content of the faces or their gender (Sato et al 2004(Sato et al , 2010Sander et al 2007; N' Diaye et al 2009;Adams et al 2012), the premotor cortex was involved in gaze and expression combination when participants were requested to attend to gaze direction (Conty et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the direction of someone's pointing finger elicits bilateral posterior superior temporal sulcus (pSTS) activation (Materna et al, 2008). Integrating someone's pointing gestures with their gaze direction recruits parietal and supplementary motor cortices in the right hemisphere (Conty et al, 2012). Together, these findings suggest an extensive right-hemisphere dominant network that is activated when one perceives a manual pointing gesture that shifts one's attention.…”
Section: Introductionmentioning
confidence: 97%
“…Previous neuroimaging studies have looked at the neural correlates of observing pointing gestures outside a referential speech context and at their integration with cues such as the gesturer's gaze direction (e.g., Brunetti et al, 2014;Conty et al, 2012;Gredebäck et al, 2010;Materna et al, 2008;Redcay et al, 2015;Sato et al, 2009). Perceiving a pointing hand compared to perceiving a non-directional closed hand elicits enhanced activation in a set of mainly right-hemisphere regions, including right inferior frontal gyrus (IFG), right angular gyrus, right parietal lobule, right thalamus, and bilateral lingual gyri (Sato et al, 2009).…”
Section: Introductionmentioning
confidence: 99%